Strategi Komunitas 9 Untuk Mengembangkan Skill santri Dalam Berdakwah - Siti Daimatul Umah; Ainur Rofiq (An-Nashiha: Journal of Broadcasting and Islamic Comunication Studies, 2022)
This Roudhotud Darajat Islamic boarding school seeks to generate students to develop skills in preaching in the community, the integration of da'wah in this Islamic boarding school is one strategy to improve aahlakul karimah, and love and care for the morals of today's youth, shown by the Nine team group in an institution. Roudhotud Darajat Islamic Boarding School. The purpose of this research is to build santri in preaching in the community and to dig deeper and understand about the use and forms of Islamic da'wah that can be done through the Nine team community at the Raudhotud Darajat Islamic Boarding School. In this study, the method used is qualitative with a phenomenological approach. Determination of data sources is determined by purposive sampling and data collection techniques used are observation, interviews and documentation.